2013
DOI: 10.9790/3008-0521017
|View full text |Cite
|
Sign up to set email alerts
|

The anti-osteoporotic effect of Moringa oliefera on osteoblastic cells: SaOS 2

Abstract: M.oliefera oliefera (MO) is a middle-sized tree, cultivated throughout

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…9 Flavanoid compound serves as an anti-inflammatory, anti oxidants and osteoprotection. [10][11][12] Several other researchers even claim that Moringa oleifera plant can inhibit cyclooxygenase enzyme, prostaglandin synthesis and nitrous oxide production in macrophages cells induced by lipopolysacaride (LPS). 12,13 Tooth extraction can cause trauma triggering inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…9 Flavanoid compound serves as an anti-inflammatory, anti oxidants and osteoprotection. [10][11][12] Several other researchers even claim that Moringa oleifera plant can inhibit cyclooxygenase enzyme, prostaglandin synthesis and nitrous oxide production in macrophages cells induced by lipopolysacaride (LPS). 12,13 Tooth extraction can cause trauma triggering inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Most experiments confirmed ethanol extract upper hand. 6,7,17,18,[22][23][24][25][26][27][28] While, Kwon research confirmed superior results for water extract of moringa over ethanolic extract (Table 2). 16 Previous studies confirmed the tissue preservation of M. oleifera leaf ethanolic extracts, for example it protected rats against the hepatotoxicity of various drugs, 9 and increased cell proliferation and cell migration of human dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 91%
“…This result is similar to the previous study which indicated that feeding of MOL to bilaterally ovariectomised rat can reduced bone loss (12) . Moreover, methanolic extracts of MO components were found to have significant osteoblast stimulating property on osteoblastic cells (13). Due to flavonoid in ethanolic extract of MOL could induce pMSCs derived from bone marrow to undergo osteogenic differentiation (14).…”
Section: Discussionmentioning
confidence: 99%